Energy Structure and Decoupling Dynamics in Emerging Economies: An Empirical Analysis of Green Growth Trajectories - Birhanu, Tagay; Reta, Birku; Mulugeta, Tsegaye (Journal of Interdisciplinary Studies, 2026)
This study uses panel regression analysis and the Tapio elasticity framework to evaluate green growth trajectories while investigating energy structure and decoupling dynamics in emerging economies. Elasticity trends from 2000 to 2024 show wildly disparate results: nations like China, Ethiopia, Rwanda, South Africa, and Uganda show strong decoupling, in line with the Environmental Kuznets Curve (EKC), while nations like Brazil, Niger, Mozambique, Vietnam, and India show negative decoupling, indicating a reliance on fossil fuels and lax regulation. In keeping with innovation theory, the random-effects GLS regression (overall R2=0.438R^2 = 0.438; Wald χ² = 98.15, p